2014
DOI: 10.1194/jlr.m048348
|View full text |Cite
|
Sign up to set email alerts
|

apoE3[K146N/R147W] acts as a dominant negative apoE form that prevents remnant clearance and inhibits the biogenesis of HDL

Abstract: apoE is a very important component of the lipoprotein transport system that has a dual functionality. It is essential for the clearance of lipoprotein remnants from the circulation ( 1, 2 ) and also promotes the biogenesis of apoEcontaining HDL ( 3 ). As a result of this and possibly other unidentifi ed functions, apoE plays a central role in atheroprotection ( 4-6 ).Lipoprotein-bound apoE is a ligand for the LDL receptor ( 7,8 ), as well as other receptors in vitro ( 9-11 ). In vivo and in vitro studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…20 Growing studies have reported that high-density lipoprotein (HDL), the smallest lipoprotein particle, tends to have fewer risks of developing cardiovascular and diabetic diseases. 21 In contrast, the low-density lipoprotein (LDL) particle is classified as bad cholesterol that can transport the lipid molecules into artery walls and attract macrophages, thereby forming atherosclerosis or inducing diabetes. 22 Therefore, lipoprotein-lowering strategy is used to inhibit the development of diabetes-related comorbidities, including DN.…”
Section: Discussionmentioning
confidence: 99%
“…20 Growing studies have reported that high-density lipoprotein (HDL), the smallest lipoprotein particle, tends to have fewer risks of developing cardiovascular and diabetic diseases. 21 In contrast, the low-density lipoprotein (LDL) particle is classified as bad cholesterol that can transport the lipid molecules into artery walls and attract macrophages, thereby forming atherosclerosis or inducing diabetes. 22 Therefore, lipoprotein-lowering strategy is used to inhibit the development of diabetes-related comorbidities, including DN.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for these individuals are limited. A recent study shows that type III hyperlipoproteinemia is induced by mutations in the LDL receptor binding domain of apoE and is characterized by inhibition of both remnant lipoprotein clearance and HDL biogenesis ( 154 ). apoE mimetic peptide therapy may be ideally suited for treatment of hypercholesterolemia associated with defects in LDL receptor function.…”
Section: Anti-atherogenic and Anti-inflammatory Effects Of Ac-he18a-nhmentioning
confidence: 99%